Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1162/nol_a_00025
|View full text |Cite
|
Sign up to set email alerts
|

Neuroplasticity in Post-Stroke Aphasia: A Systematic Review and Meta-Analysis of Functional Imaging Studies of Reorganization of Language Processing

Abstract: Recovery from aphasia is thought to depend on neural plasticity, that is, functional reorganization of surviving brain regions such that they take on new or expanded roles in language processing. We carried out a systematic review and meta-analysis of all articles published between 1995 and early 2020 that have described functional imaging studies of six or more individuals with post-stroke aphasia, and have reported analyses bearing on neuroplasticity of language processing. Each study was characterized and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 188 publications
8
69
0
1
Order By: Relevance
“…These cross-sectional chronic results also complement studies of spontaneous aphasia recovery that found a recovery trajectory in which good outcomes in the chronic phase were correlated with taskrelated activity returning to normal levels (Saur, 2006;Stockert et al, 2020). More broadly, these findings are consistent with a recent review of aphasia recovery, which found that lesions caused overall reduced activation in people with aphasia, with activity in left-hemisphere language regions relating to better language function (Wilson & Schneck, 2021).…”
Section: Dysfunction and Partial Normalization Of The Typical Left Hemisphere Language Networksupporting
confidence: 85%
“…These cross-sectional chronic results also complement studies of spontaneous aphasia recovery that found a recovery trajectory in which good outcomes in the chronic phase were correlated with taskrelated activity returning to normal levels (Saur, 2006;Stockert et al, 2020). More broadly, these findings are consistent with a recent review of aphasia recovery, which found that lesions caused overall reduced activation in people with aphasia, with activity in left-hemisphere language regions relating to better language function (Wilson & Schneck, 2021).…”
Section: Dysfunction and Partial Normalization Of The Typical Left Hemisphere Language Networksupporting
confidence: 85%
“…The bulk of neuroimaging studies investigating patterns of reorganization associated with language recovery in aphasia have used task-based functional magnetic resonance imaging (fMRI; Wilson and Schneck, 2020). fMRI has clearly been valuable for studying neuroplasticity in this population.…”
Section: Introductionmentioning
confidence: 99%
“…In the language tasks, several different activation patterns were expected. Extrapolated from fMRI studies, individuals with aphasia were hypothesized to recruit spared left hemisphere language regions (i.e., LIFGtri, LIFGoper, LPCG, LMTG, LAG, Sebastian and Kiran, 2011;Sims et al, 2016;Wilson and Schneck, 2020), right hemisphere homologous language regions (i.e., RMTG; Sebastian and Kiran, 2011) and/or domain-general areas (i.e., LMFG, LIFGoper, BLPCG, LSMG, LAG; Meier et al, 2016Meier et al, , 2018Meier et al, , 2019 while naming or judging semantic features of real pictures. In the arithmetic task, they were anticipated to activate regions in the spared domaingeneral network when solving hard versus easy addition problems with potential for diminished extent or magnitude of activation relative to healthy controls (Blank et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Neuroplasticity allows the brain to reorganize speech circuits disrupted by stroke and is a driving force behind recovery from motor speech disorders ( Hartwigsen and Saur, 2019 ; Wilson and Schneck, 2021 ). Though speech production is heavily lateralized to the left hemisphere, increases in neuroplasticity during speech therapy can shift speech processing toward the right hemisphere ( Anglade et al, 2014 ; Wan et al, 2014 ).…”
Section: Plasticity Underlies Functional Improvements Of Motor Speech Control Recoverymentioning
confidence: 99%